Anais Do Ii Congresso on-Line Nacional De Saúde Multidisciplinar (Ii Conasmulti) 2023
DOI: 10.53524/lit.edt.978-65-84528-20-8/25
|View full text |Cite
|
Sign up to set email alerts
|

Relevância Da Educação Em Saúde No Cuidado De Enfermagem Frente Ao Câncer De Ovário

Abstract: A organização do II Congresso On-line Nacional de Saúde Multidisciplinar (II CONASMULTI) não assume qualquer responsabilidade pelo teor ou possíveis erros de linguagem dos trabalhos divulgados na presente obra, a qual recai, com exclusividade, sobre seus respectivos autores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the present study, almost 95% of the students reported that they were unable to perform some procedures they were adept at, and more than 70% had difficulties concentrating on academic activities. Medeiros et al, 2021 [8] reported that the suspension of clinical and laboratory sessions/classes significantly affected learning and impacted dental education. [17] stated that with regard to the repercussions on academic life, risk of infection for students participating in coping with the pandemic, disruption of the study routine, postponement of tasks and academic activities, and delay in the schedule of courses has repercussions on future professional plans and on the search for independence and financial stability, which is occasionally fostered in the expectation of university education leading to a feeling of frustration in academics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, almost 95% of the students reported that they were unable to perform some procedures they were adept at, and more than 70% had difficulties concentrating on academic activities. Medeiros et al, 2021 [8] reported that the suspension of clinical and laboratory sessions/classes significantly affected learning and impacted dental education. [17] stated that with regard to the repercussions on academic life, risk of infection for students participating in coping with the pandemic, disruption of the study routine, postponement of tasks and academic activities, and delay in the schedule of courses has repercussions on future professional plans and on the search for independence and financial stability, which is occasionally fostered in the expectation of university education leading to a feeling of frustration in academics.…”
Section: Resultsmentioning
confidence: 99%
“…In undergraduate dentistry courses, students had to deal with delays in course completion because of suspended laboratory and clinical training. In Brazil alone, 1,25,585 dentistry students were without classes/lectures for almost a year [8]. Switching to online learning, varying study loads, lack of practice during the pandemic negatively impacted students' lives and caused stress, anxiety disorder, and depression in many of them [6,7,9,10].…”
Section: Coronavirus Disease 2019 (Covid-19mentioning
confidence: 99%